Experimental investigation of fish downstream passage and turbine related fish mortality at an innovative hydro power setup. Issue 6 (1st December 2016) - Geiger, Franz; Cuchet, Mathilde; Rutschmann, Peter
Abstract : The fish downstream passage of small fish at the innovative TUM hydro shaft power plant concept was investigated experimentally. The behavior of 1974 inserted individuals of brown trout, grayling, barbel, minnow and bullhead of 45 mm to 220 mm body length was observed in a fully functional test setup which included a 35 kW Kaplan turbine and a horizontal screen with 20 mm bar clearance. The 24 h tests were conducted under nature like conditions whereas the laboratory environment also enabled targeted hydraulic situations and modifications of the bypass during the test series. A recapture rate of the fish of 99% and a subsequent 96 h observation period yielded detailed information about the migration behavior and instant as well as long term mortality. The results reveal the actual passage distribution of small fish between bypass and turbine and the turbine related injury and mortality rates in dependency of fish species, fish length, turbine discharge and bypass arrangement. General trends as well as species specific particularities could be deduced. The work confirms the suitability of the employed experimental approach and the ecological potential of the investigated hydro power plant concept. The behavioral barrier effect of the screen on small fish and the necessaty of appropriate downstream migration corridor were proved and quantified.